SAT0725-HPR Gothenburg nurse led tight control study - gotnet. a study comparing "care as usual" with nurse led clinic, tight control and person centred care in patients with rheumatoid arthritis (RA) and with moderate/high disease activity. (15th June 2017) - Bergsten, U; Almehed, K; Jacobsson, L
Abstract : Background: The treatment guidelines of EULAR recommend treatment according to "tight control" (TC), clear treatment goals (Treat-to-Target, T2T) and patient involvement. Despite this, the care for patients with RA needs to be improved as demonstrated by the fact that as many as that 45% of patients with RA in Sweden (according to the Swedish Rheumatology Quality Register in 2015) do not reach the level of low disease activity. One way to overcome this could be nurse led clinics of RA patients, which for patients in remission have shown positive effects on patient's pain, knowledge and self-efficacy. We hypothesized that a nurse-led clinic based on the above principles of TC, T2T and Person-centered care would result in better outcome compared to care as usual. Objectives: The aim of the study was to compare the effect of such nurse-led clinic with frequent visits and person-centered care with regular care of patients with established RA and a moderate to high disease activity. Methods: This was a randomized, controlled, blinded assessor study that aimed to compare the effect of nurse-led clinic with regular care of patients with the established RA. Inclusion criteria were; duration of RA >2 yrs., DAS28>3.8, age <85 yrs. and not having experience with all available csDMARDs and bDMARDS. Patient with any severe current comorbidity were excluded. Intervention Group (IG): intervention included two elements; 1) disease activity control every 6th week, with clear treatment goals (DAS28 <2.6)and escalation of pharmacological therapy according to existing Swedish guidelines, 2) a written person-centered care health plan with shared goal setting and decision making between patient and nurse. Control Group (CG): Patients in the control group were followed by a physician once every 3 to 6 month. Evaluation was done at w 26 both per protocol (shown) and according to intention to treat (ITT) with LOCF. Primary outcome was change in DAS28 at week 26 and secondary outcome the proportions of good/moderate EULAR response. Pre study power calculations estimated group sizes to 60 patients in each group. Due to difficulties in the recruiting process the study was stopped preterm Results: The study included 70 patients of which (IG: 36 and CG: 34) with similar baseline characteristics as a result of the randomization. Sixty-two patients completed the study at w 26 (IG: 29 and CG: 33). Both groups improved significantly in DAS 28 (Table 1 ). The change in DAS 28 was not significantly different between groups, although the numerical improvement was larger in the IG compared to CG (Table 1 ). Furthermore, significantly more patients in the IG improved according to EULAR Good or Moderate response (Table 1 ). Results were similar when analyzing according to ITT with LOCF. Conclusions: This controlled trial suggest that a nurse-led clinic for RA patients with moderate/high disease activity may be effective. Although not shown, it likely to be cost-effective and possible to implement in clinical care. Disclosure of Interest: None declared